DFT-Based Calculation of Dissolution Activation Energy and Kinetics of Ni–Cr Alloys. Issue 13 (5th October 2020) - Ke, Huibin; Taylor, Christopher D.
Abstract : A density functional theory investigation of the process of dissolution of Ni and Cr adatoms from model Ni–Cr(111) alloy surfaces is presented, both in vacuum and with explicit water molecules. The goal is to understand how the electronic structures solved using DFT can provide insights as to changes in valence, energy and coordination of the adatoms in the process of dissolving from the alloy surface. It is found that nearby Cr solute atoms increase the dissolution activation energy of Ni. Cr adatoms have a similar dissolution activation energy as Ni adatoms, except for one particular surface configuration that has a much smaller dissolution activation energy, which might promote selective dissolution of Cr in Ni–Cr alloys. To interpret the first-principles modeling results for the potential energy trajectory along the dissolution reaction coordinate, we provide a thermodynamic breakdown of the various terms that contribute to the dissolution activation and total reaction energy. The role of addition of Cr is explored on the dissolution kinetics of a Ni–Cr alloys of varying composition by constructing a model for the corrosion current density with DFT-based activation energies. Finally, dissolution resistance index is proposed as a quantifiable descriptor of the dissolution resistance of corrosion resistant alloys.